Sensing qualia - Skokowski, P (Frontiers Media, 2022)
Accounting for qualia in the natural world is a difficult business, and it is worth understanding why. A close examination of several theories of mind-Behaviorism, Identity Theory, Functionalism, and Integrated Information Theory-will be discussed, revealing shortcomings for these theories in explaining the contents of conscious experience: qualia. It will be argued that in order to overcome the main difficulty of these theories the senses should be interpreted as physical detectors. A new theory, Grounded Functionalism, will be proposed, which retains multiple realizability while allowing for a scientifically based approach toward accounting for qualia in the natural world.